1996
DOI: 10.1007/bf00041384
|View full text |Cite
|
Sign up to set email alerts
|

Plant cyclins: a unified nomenclature for plant A-, B- and D-type cyclins based on sequence organization

Abstract: The comparative analysis of a large number of plant cyclins of the A/B family has recently revealed that plants possess two distinct B-type groups and three distinct A-type groups of cyclins. Despite earlier uncertainties, this large-scale comparative analysis has allowed an unequivocal definition of plant cyclins into either A or B classes. We present here the most important results obtained in this study, and extend them to the case of plant D-type cyclins, in which three groups are identified. For each of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
167
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(170 citation statements)
references
References 65 publications
1
167
0
2
Order By: Relevance
“…To examine whether the activity of NtmybA2 might be controlled by cyclins, we cotransfected BY2 protoplasts with expression plasmids for full-length NtmybA2 and expression plasmids for various tobacco cyclins. In plants, cyclins A, B, and D are encoded by multigene families, each of which is further subdivided into three to seven subfamilies on the basis of amino acid sequences and expression profiles during the cell cycle (35,36). It is believed that plants do not have cyclin E, because the Arabidopsis genome does not contain genes that are homologous to animal cyclin E. In this study, we examined the effects of cyclins from the B1-, A1-, A2-, A3-, and D3-type subfamilies from tobacco, which are herein designated CycB1, CycA1, CycA2, CycA3, and CycD3, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether the activity of NtmybA2 might be controlled by cyclins, we cotransfected BY2 protoplasts with expression plasmids for full-length NtmybA2 and expression plasmids for various tobacco cyclins. In plants, cyclins A, B, and D are encoded by multigene families, each of which is further subdivided into three to seven subfamilies on the basis of amino acid sequences and expression profiles during the cell cycle (35,36). It is believed that plants do not have cyclin E, because the Arabidopsis genome does not contain genes that are homologous to animal cyclin E. In this study, we examined the effects of cyclins from the B1-, A1-, A2-, A3-, and D3-type subfamilies from tobacco, which are herein designated CycB1, CycA1, CycA2, CycA3, and CycD3, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mature silique dimensions were determined by using a digital micrometer. To detect the influence of the ppd mutation on cell proliferation, a CYCB1,1::GUS reporter gene (29) was introgressed into WT and mutant backgrounds. Histochemical detection of GUS activity was carried out as described by Donnelly et al (1).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 6A, R2 (encoding a cyclin-dependent kinase-activating kinase, which regulates S-phase progression and controls cell division [34]) expression was three times higher in lc2-1 plants compared to WT, which was restored to normal level by complementary expression of LC2. Analysis of the expression of CDKA;1 and CDKA;2 (two known cdc2 protein kinases; CDKA;2 is possibly responsible for the induction of G 1 -to S-phase transition [35,36]) revealed that the pattern of CDKA;2 was similar to R2 ( Figure 6A, upper panel), whereas the transcript level of CDKA;1 was not obviously altered ( Figure 6A, bottom panel). However, H4, H3 (two molecular markers for the S phase [36]), and EXPB6 (a member of the β-expansin gene family critical for cell elongation in deep water rice [37]) expressions were not obviously altered in the lc2-1 mutant ( Figure 6A, bottom panel).…”
Section: Lc2 Is Expressed In Aerial Parts and Induced By Hormonesmentioning
confidence: 99%